Predicting public relations crises through artificial intelligence applications - Leith Sabbar Jabeer ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The research is interested in defining a clear scientific vision of the importance of employing artificial intelligence applications by public relations practitioners in government institutions, as well as studying its importance in predicting and managing crises, and identifying the most intelligent applications that will be relied upon in the future and the challenges they face, as the research results showed that the percentage 78% of the respondents preferred the priority of their answers to the category (I agree) that artificial intelligence applications perform complex tasks that require human participation in their work to improve their performance. The results also showed that 78% of the respondents preferred the priority of their answers to the category (I agree) that artificial intelligence applications predict crises. before they occur and provide mechanisms that work to confront them, while most of the respondents did not agree on the existence of legal frameworks capable of achieving societal security and preventing misuse of these applications .